2007
DOI: 10.1111/j.1540-4560.2007.00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Judgmental Discounting and Environmental Risk Perception: Dimensional Similarities, Domain Differences, and Implications for Sustainability

Abstract: Environmental risks constitute a special category of risks because they often involve consequences that are highly uncertain, strongly delayed, occurring at distant places, and-therefore-mostly borne by others. Economic, decision-theoretic, and psychological research about the way people deal with such consequences is reviewed. Two major findings are presented: first, there is evidence that discounting mechanisms are stable across different preference dimensions (uncertainty, temporal, spatial, and social dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(95 citation statements)
references
References 70 publications
5
82
1
4
Order By: Relevance
“…The low discount rates observed may thus have been due to the difference in valence (as gains are typically discounted more than losses; Thaler, 1981) or the difference between who was affected by the consequences (others vs. self). Similarly, in a brief review of temporal discounting studies, Gattig and Hendrickx (2007) concluded that discounting is less pronounced for environmental risks than for other domains, noting that a substantial proportion of participants (in the range of 30% to 50%) do not discount environmental risks at all. However, none of the articles reviewed directly compared monetary and environmental outcomes nor did they control for potentially confounding factors such as the valence of outcomes.…”
Section: Domain Differences In Time Preferences?mentioning
confidence: 99%
“…The low discount rates observed may thus have been due to the difference in valence (as gains are typically discounted more than losses; Thaler, 1981) or the difference between who was affected by the consequences (others vs. self). Similarly, in a brief review of temporal discounting studies, Gattig and Hendrickx (2007) concluded that discounting is less pronounced for environmental risks than for other domains, noting that a substantial proportion of participants (in the range of 30% to 50%) do not discount environmental risks at all. However, none of the articles reviewed directly compared monetary and environmental outcomes nor did they control for potentially confounding factors such as the valence of outcomes.…”
Section: Domain Differences In Time Preferences?mentioning
confidence: 99%
“…A popular solution for loss aversion is to subtly adjust default policy options and organizational settings toward more ecologically responsible defaults (Gattig andHendrickx 2007, Cornforth 2009). People tend to stick with default option settings because of loss aversion, status quo bias, and other reasons.…”
Section: Strategic Framingmentioning
confidence: 99%
“…Environmental risk represents the probability to suffer potential negative effects due to changes in the environment [40]. Environmental risks form a distinct group and have specific features: high levels of uncertainty and uncontrollability, strongly delayed consequences, and consequences that occur at distant places and that are, therefore, often borne more by others than by the ones who caused them [41].…”
Section: From Risk Perception To Environmental and Radon Risk Perceptmentioning
confidence: 99%